A comunicação entre parceiros que são pais e mães de adolescentes - Gonçalves, Laura Guerrelhas (Universidade Federal de São Carlos, 2025)
Difficulties in helping a teenage child can generate tensions between the parents, reducing the quality of the coparenting relationship and affecting the emotional bond between the parents. Thus, skills for managing the stress itself, during interactions between partners, may be important. However, in the existing literature, there is little evidence about these skills and how they affect the coparenting relationship. The objectives of this study, therefore, are: (a) to evaluate the perceptions of fathers and mothers who have teenage children about their dyadic coping skills, each partner's involvement in maintaining the coparenting relationship, and the quality of this relationship; and (b) to investigate the relationships between these three constructs. As such, 107 mothers and fathers of a teenage child, who resided with their partner, completed: a sociodemographic questionnaire, the Dyadic Coping Inventory, a questionnaire on parental involvement in managing the coparenting relationship, and the Coparenting Relationship Scale, via Google Forms. The scores of mothers and fathers were compared, using the Mann-Whitney U test, and the relationships between dyadic coping, engagement in managing the coparental relationship, and the quality of the coparental relationship were verified, using Spearman's test of correlation. There were no significant gender differences involving the Dyadic Coping instrument, although both fathers and mothers considered that women were less open than men to communication about stressful situations involving their adolescent child. With respect to relationship engagement, men reported initiating conversations with the same frequency as their partner, whereas women reported initiating conversations significantly more frequently than their partner. In addition, women evaluated the division of labor related to parenting their adolescent child less positively than men. Correlations were found between the six dimensions of dyadic coping and seven dimensions of coparenting for both genders, but these relationships were both more numerous and of greater strength for women than for men. Thus, mothers’ and fathers’ perceptions of how their partner responds to concerns involving an adolescent child contribute to their perceptions of the quality of the coparenting relationship, with a stronger effect for women than for men. Considering that these constructs are related, especially in the case of mothers, these findings support the development and evaluation of interventions aimed at strengthening emotional management skills during interactions between coparenting partners who experience frequent conflict, as a way of contributing to the professional practice of psychologists working with families with adolescents.
Communication between partners who are mothers and fathers of adolescents
Keywords: Relação coparental; Parentalidade; habilidades interpessoais; estresse parental; adolescência; Coparenting Relationship; Parenting; Interpersonal Skills; Parenting Stress; Adolescence; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::RELACOES INTERPESSOAIS; 3. Saúde e Bem-Estar; 5. Igualdade de Gênero